1998
DOI: 10.1046/j.1526-4610.1998.3801003.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Treatment of Refractory Cluster Headache

Abstract: Four men and two women were treated for refractory cluster headache by gamma knife radiosurgery of the trigeminal nerve root entry zone. The maximum dose of radiation was 70 Gy to the isocenter. Of five patients treated who had refractory chronic cluster headache and one with refractory episodic cluster headache, four had relief judged excellent. Of the two remaining patients with refractory chronic cluster headache, one had relief judged good and the other fair. Five of the six patients treated had relief wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 1 publication
1
40
1
Order By: Relevance
“…Gamma knife radiosurgery of the trigeminal nerve root entry zone has been reported in 5 chronic CH patients with neglible short-term and long-term sequelae (Ford et al 1998). …”
Section: Destructive Proceduresmentioning
confidence: 99%
“…Gamma knife radiosurgery of the trigeminal nerve root entry zone has been reported in 5 chronic CH patients with neglible short-term and long-term sequelae (Ford et al 1998). …”
Section: Destructive Proceduresmentioning
confidence: 99%
“…Gamma knife SRS has been proposed as a minimally invasive alternative management option for CH (Table 1) [4,[30][31][32][33]. Ford et al [32] reported six refractory CH patients, four of whom achieved excellent pain relief, one good pain relief, and one fair pain relief days to weeks after SRS.…”
Section: Stereotactic Radiosurgery For Cluster Headachementioning
confidence: 99%
“…Ford et al [32] reported six refractory CH patients, four of whom achieved excellent pain relief, one good pain relief, and one fair pain relief days to weeks after SRS. No patient had significant side effects when studied 8 to 14 months afterwards.…”
Section: Stereotactic Radiosurgery For Cluster Headachementioning
confidence: 99%
“…Previously used approaches have included trigeminal ganglion glycerol injections, 10,11 radiofrequency rhizotomy of the Gasserian ganglion 12 or gamma knife aimed at the trigeminal nerve, 13,14 microvascular decompression 15 and esection or blockade of the N. petrosus superficialis 16 or pterygopalatine (sphenopalatine) ganglion. [17][18][19] There are case series of trigeminal nerve root section to the episodic form, 23 so a procedure should not be less safe than the natural history.…”
Section: What Approaches Have Been Tried?mentioning
confidence: 99%